Allelopathic Effect of Parthenium hysterophorus on Germination and Growth of Some Important Crops and Weeds of Economic Importance - HASSAN,G. (2018)
ABSTRACT: Parthenium hysterophorus being a declared invasive weed worldwide is threatening the biodiversity of Pakistan. To study its allelopathic potential, laboratory and pots based studies were undertaken during July-August and October-November, 2010 in Weed Research Laboratory, Department of Weed Science, The University of Agriculture Peshawar, Khyber Pakhtunkhwa Pakistan. The experiments were conducted to investigate the allelopathic effect of parthenium on crops Triticum aestivum, Cicer arietinum and Brassica campestris, and weeds including Avena fatua, Asphodelus tenuifolius and Lolium rigidum The fresh leaves of P.hysterophorus were dried in shade and grinded. The desired quantity of powder was soaked for 16 hr. in the desired quantity of water to make the stock solution of the maximum concentration viz. 75 g L-1. Five seeds of each species were placed in Petri dishes and in pots, extracts were applied when needed. Control (0 g L-1) was also included for comparison. Both experiments were laid out as Factorial in completely randomized design (CRD) with four replications and two runs each. Since the statistical differences between the runs were non-significant the data were pooled before subjecting it to ANOVA and mean separation. The differences among the test species and the rates of parthenium extracts were different statistically (P?0.05) for all the traits examined, while for the species x parthenium concentration interaction, the differences were only significant (P?0.05) for plant height in the pot experiment. The results showed that with the increasing concentration of P. hysterophorus, all the parameters studied in the six test species were significantly decreased. Hence, the present study suggests that P. hysterophorus affects the agro-ecosystem and needs to be properly managed, moreover, its allelopathy on weeds is an encouraging finding for the weed managers for the sustainable management of weeds.